Tezepelumab improved chronic eosinophilic pneumonia in severe asthma patients with liver cirrhosis - Inaba, Mizuki; Shimizu, Yasuo; Nakamura, Yusuke; Okutomi, Hiroaki; Takemasa, Akihiro; Niho, Seiji (Frontiers in Medicine, 2024)
Systemic administration of corticosteroids is used in the treatment of chronic eosinophilic pneumonia (CEP). However, in patients with CEP as well as other comorbidities, the adverse effects of corticosteroids should be minimized as much as possible. A 71-year-old woman presented aggravating asthma with CEP and sinusitis, and she had uncompensated liver cirrhosis (LC) with a Child-Pugh score of 7. Initial treatment with a low dose of oral corticosteroids (OCS) in combination with tezepelumab, an anti-thymic stromal lymphopoietin (TSLP) antibody, resulted in rapid improvement of asthma and CEP without deteriorating LC. Sinusitis also improved after ceasing OCS. This case suggested that tezepelumab may be useful as a treatment option for patients with CEP, especially having liver dysfunction.